An Economist's Perspective on Student Loans in the United States - Susan M. Dynarski (Center for Economic Studies and ifo Institute (CESifo), 2015)
In this paper, I provide an economic perspective on policy issues related to student debt in the United States. I lay out the economic rationale for government provision of student loans, summarize time trends in student borrowing, describe the US loan market, then turn to topics central to the policy discussion of student loans: whether there is a student debt crisis, the costs and benefits of interest subsidies, and the suitability of an income-based repayment system for student loans. I close with a discussion of the gaps in the data required to fully analyze and steer student-loan policy.
Keywords: 330; student debt; student loans; subsidies